2019
DOI: 10.3747/co.26.5107
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Trifluridine/Tipiracil for Patients with Metastatic Colorectal Cancer in Canada

Abstract: Background Outcomes for patients with metastatic colorectal cancer (mcrc) are improving with the introduction of new treatments. Treatment for patients who are still fit after failure of all available therapies represents a significant unmet need. In the present study, we analyzed real-world treatment patterns for patients enrolled in Health Canada’s trifluridine/tipiracil (ftd/tpi) Special Access Program (sap) and Taiho Pharma Canada’s Patient Support Program (psp).Methods Demographic information and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
4
4
0
1
Order By: Relevance
“…Meanwhile, the median PFS of our cohort was concordant with that of patients with advanced gastric/gastroesophageal cancer treated with FTD/TPI alone in recent Denmark-and Japan-based studies [26,27]. Prolonged FTD/TPI treatment durations in compassionate use programs versus clinical trial cohorts have been well-documented in metastatic colorectal cancer [28][29][30][31], and may be by virtue of the enhanced feasibility of administration in non-trial settings. Although we could not examine treatment outcomes relative to a comparator group, treatment duration and PFS in our cohort were both longer than expected and, together, represent evidence of drug effectiveness in practice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Meanwhile, the median PFS of our cohort was concordant with that of patients with advanced gastric/gastroesophageal cancer treated with FTD/TPI alone in recent Denmark-and Japan-based studies [26,27]. Prolonged FTD/TPI treatment durations in compassionate use programs versus clinical trial cohorts have been well-documented in metastatic colorectal cancer [28][29][30][31], and may be by virtue of the enhanced feasibility of administration in non-trial settings. Although we could not examine treatment outcomes relative to a comparator group, treatment duration and PFS in our cohort were both longer than expected and, together, represent evidence of drug effectiveness in practice.…”
Section: Discussionsupporting
confidence: 81%
“…At our data cut-off date, 39 patients (24%) never received FTD/TPI, despite enrolling in the program initially. The foremost reason, death, parallels the findings of a previous study from our group on FTD/TPI use in refractory metastatic colorectal cancer [28]. It also reinforces the necessity of timely treatment for advanced gastric/gastroesophageal cancer, whether to palliate or prolong survival.…”
Section: Discussionsupporting
confidence: 80%
“…Median PFS was 2.8 months, an improvement on the results of RECOURSE. Other data available include published retrospective data, meta-analysis and abstracts [ 10 , 11 , 12 , 13 , 14 , 15 ]. Their reported outcomes are summarised in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with refractory mcrc have an unmet need and high demand for a tolerable therapy. A previous study reported that more than 700 Canadian patients applied for the drug through the tcan patient support program over a 12-month period 9 . As of February 2020, the number of patients who have accessed ftd/tpi through the tcan patient support program has increased by 1497, including 982 patients who received ftd/tpi in 2019, most with mcrc.…”
Section: Introductionmentioning
confidence: 99%